Error correction and repair moves in synchronous learning activities (2018)
ABSTRACT: Language teaching is a field in constant evolution, and the use of technology has boosted its development. However, there is a need to investigate the effects of technology on the development of pedagogical practices and their effects on learning outcomes. This study explores the deployment of correction strategies and repair moves in synchronous learning activities in an online English course. The study uses a mixed-methods approach that combines qualitative and quantitative research methods. The main findings of this investigation show that synchronous learning activities prompt the production of explicit corrections. The results also show that the deployment of explicit corrections generate the production of repair moves that lead to learning.